2016
DOI: 10.1080/13621718.2015.1123443
|View full text |Cite
|
Sign up to set email alerts
|

Welding distortion and inherent deformation under temporary tacking and its released states

Abstract: In the present study, the detailed welding distortion of bead welded plates under temporary tacking state and released state was predicted by thermal elastic-plastic finite element model (FEM) and also measured by the digital image correlation (DIC) method. It was found that the residual welding angular distortion can be reduced to about 50-60% by temporary tacking, while the residual transverse shrinkage and longitudinal shrinkage are less affected. Further, the welding distortion with different ratios of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Deng et al [8] predicted welding distortion of a large thin-plate panel structure by the elastic FEM based on the inherent strain theory and found that the large deformation theory should be carefully considered; furthermore, the simulation results indicate that both welding procedure and assembly sequence significantly affect the final deformation. Ma et al [9] studied the welding distortion of bead welded plates under temporary tacking state and released state by thermalelastic-plastic FEM. It was found that the residual welding angular distortion can be reduced greatly by temporary tacking, while the residual transverse shrinkage and longitudinal shrinkage are less affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al [8] predicted welding distortion of a large thin-plate panel structure by the elastic FEM based on the inherent strain theory and found that the large deformation theory should be carefully considered; furthermore, the simulation results indicate that both welding procedure and assembly sequence significantly affect the final deformation. Ma et al [9] studied the welding distortion of bead welded plates under temporary tacking state and released state by thermalelastic-plastic FEM. It was found that the residual welding angular distortion can be reduced greatly by temporary tacking, while the residual transverse shrinkage and longitudinal shrinkage are less affected.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al. [9] studied the welding distortion of bead welded plates under temporary tacking state and released state by thermal-elastic–plastic FEM. It was found that the residual welding angular distortion can be reduced greatly by temporary tacking, while the residual transverse shrinkage and longitudinal shrinkage are less affected.…”
Section: Introductionmentioning
confidence: 99%
“…Pal S [8] used the Taguchi method to optimize parameters on PMIGW and the response measured were angular distortion, transversal shrinkage, bead geometry, deposition efficiency, and tensile strength. Analyzing distortions that occur can be applied using FEM [9], and the results show that the angular distortion can decrease due to temporary tacking.…”
Section: Introductionmentioning
confidence: 99%
“…Recentes trabalhos quanto à simulação numérica e busca para a predição das deformações na soldagem são concentrados em distorções de chapas paralelas ou grandes estruturas, exemplificando no trabalho de Zubairuddin et al (2017) que realizaram análise numérica com a soldagem multi passe de junta de chapas paralelas e obtiveram uma correlação de predição de distorção por meio do modelo numérico. Ma et al (2016) realizaram estudos numéricos quanto à predição de distorções em estruturas sujeitas às restrições temporárias e obtiveram boa correlação entre os resultados numéricos e experimentais.…”
Section: Introductionunclassified